EFEKTIVITAS PEMBELAJARAN MENGGUNAKAN PLATFORM EDUKASI DIGITAL UNTUK MENINGKATKAN KREATIVITAS PESERTA DIDIK DI MAN 1 MANDAILING NATAL - Aisyah, Siti; Kasman; Septrisia, Reni (Program Studi Manajemen Pendidikan Islam (MPI) STAI Nahdlatul Ulama (STAINU) Malang, 2025)
This research aims to determine the effectiveness of the learning process using digital education platforms, which is very important for the smoothness and continuity of the learning process because learning effectiveness is one of the educational quality standards that must be carried out in managing the learning process. This research was carried out at MAN 1 Mandailing Natal which is located in Dalan Lidang. The type of research used is quantitative using experimental methods and a non-equivalent control group research design. Sampling was carried out using a purposive sampling technique and the way to determine the number of samples in this research was by using gay and airasian theory. The number of samples used in this type of experimental research was 30 people per each group. One class is used as the experimental class and one class is used as the control class. Class XI IPS 1 as an experimental class has a total of 36 students and class . The research results obtained from the learning outcomes of students in economics subjects in Class Class posttest using digital education platforms in learning is quite effective in improving student learning outcomes in class XI MAN 1 Mandailing Natal. So it can be concluded that there is an influence of learning using digital education platforms to increase students' creativity at MAN 1 Mandailing Natal.